Properties and homogeneity of a commercial light expanded clay aggregate - Sosa Fabré, Evelin Noelí (2024)
In the present work, an exhaustive analysis of an Argentinian commercial LECA with a multi-technique approach was successfully carried out. Five sub-types of samples were considered to study the degree of macroscopic homogeneity of the LECAs, which presented observable differences in color and morphology. The microstructural, textural, and mineralogical features of the aggregates within each category were assessed and the differences among them were described and discussed. The density values of the samples studied were between 1.01 and 1.20 g/cm3 and porosity percentages were in the range of 24 to 33 %. The samples present a similar mineralogical composition with quartz and anorthite as the main crystalline phases and almost 50 wt. % of non-crystalline phase. In addition, some variations in the Rietveld quantification were analyzed. The main challenge of LECAs industrial production is to control the raw materials and the process to obtain homogeneous LECAs with similar performance. In this regard, this type of analysis is useful for establishing and comparing some characterization strategies to control, select, design, and evaluate new LECAs.